The effect of regular increased physical activity, and regular consumption of ready-to-eat-cereal (RTEC) breakfasts and afternoon snacks on the weight of young adolescents attending public Gauteng schools - Philippou, Androulla (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Human Nutrition))--Stellenbosch University, 2008.